TOWARDS A STRONG ECONOMIC SYSTEM: Revealing the Logic of Gratuitousness in the Market Economy - Chackalackal, Saju; Mascarenhas, Theodore (Asian Horizons, 2011)
The international colloquium on “Towards a Strong Global Economic System: Revealing the Logic of Gratuitousness in the Market Economy” was attended by 150 delegates, experts, and participants from all over the world. The event was jointly organized by the Pontifical Council for Culture (Vatican), Dharmaram Vidya Kshetram (Bangalore), and Christ University (Bangalore). Organized by Pontifical Council for Culture (Vatican), Dharmaram Vidya Kshetram (Bangalore) and Christ University (Bangalore) 25-29 October, 2011, Bangalore India. Venue: Christ University and Dharmaram Vidya Kshetram (Bangalore)